2016
DOI: 10.1016/j.fct.2016.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of endpoints relevant to toxicity assessments in 3 generations of CD-1 mice fed irradiated natural and purified ingredient diets with varying soy protein and isoflavone contents

Abstract: Diet is an important variable in toxicology. There are mixed reports on the impact of soy components on energy utilization, fat deposition, and reproductive parameters. Three generations of CD-1 mice were fed irradiated natural ingredient diets with varying levels of soy (NIH-41, 5K96, or 5008/5001), purified irradiated AIN-93 diet, or the AIN-93 formulation modified with ethanol-washed soy protein concentrate (SPC) or SPC with isoflavones (SPC-IF). NIH-41 was the control for pairwise comparisons. Minimal diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…Mice food was in the form of pellets. Genistein supplemented diet as well as control diets were sterilized by irradiation (20-50kGY) as recommended by Teklad Envigo [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mice food was in the form of pellets. Genistein supplemented diet as well as control diets were sterilized by irradiation (20-50kGY) as recommended by Teklad Envigo [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…As semi‐purified diets are generally favoured because they provide more uniformity and reproducibility, we used semi‐purified diet in our study. There are several studies reported in the literature using semi‐synthetic diets for various experimental purposes in various experimental animal models (Camacho et al, ; Chan, ; Del Bas et al, ; Horton, Cuthbert, & Spady, ; Kang, Shin, Park, & Lee, ; Kopeć & Leszczyńska, ; Krasnow, Nguyen, & Marks, ; Mawatari et al, ; Muga & Chao, ; Rousseaux, Schiefer, & Hancock, ; Wang, Jones, Pischel, & Fairow, ).…”
Section: Discussionmentioning
confidence: 99%
“…Cornstarch as a source of carbohydrate is commonly used for many of the studies using semi‐synthetic diets in rats and mice (Annapurna et al, ; Camacho et al, ; Del Bas et al, ; Kang et al, ; Kopeć & Leszczyńska, ; Krasnow et al, ; Mawatari et al, ; Rousseaux et al, ; Venu et al, ). In studies carried out in rats, although two widely used control diets, a semi‐purified diet (SD) or chow‐based diet (ND) produced very different outcomes in the lipid metabolism of lactating rats and their offspring, energy intakes, growth and fertility were not affected (Del Bas et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…b Mean body weights at the later time points, weeks 36 to 52, were 10-13% higher than control means in the 2.5 μg BPA/kg bw/day. The Dunnett-corrected p-values were 0.080, 0.058, 0.071, 0.065, and 0.062, for weeks 36 75 ± 1 (50) 76 ± 1 (48) 78 ± 1 (46) 76 ± 1 (49) 74 ± 1 (50) 76 ± 1 (46) 76 ± 1 (26) 80 ± 2 * (26) 8 196 ± 3 (50) 201 ± 3 (48) 202 ± 2 (46) 199 ± 2 (49) 198 ± 3 (50) 204 ± 3 b (45) 200 ± 4 (26) 212 ± 4 * (26) 12 266 ± 4 (50) 269 ± 4 (48) 270 ± 4 (46) 267 ± 3 (49) 266 ± 4 (50) 269 ± 3 (45) 269 ± (26) 268 ± 6 (26) 16 302 ± (50) 305 ± 5 (47) 303 ± (46) 299 ± 3 (49) 300 ± (50) 302 ± 4 (45) 299 ± (26) 299 ± 7 (26) 20 324 ± 6 (50) 327 ± 6 (47) 325 ± 6 (46) 319 ± 4 (49) 319 ± 5 (50) 321 ± 4 (45) 320 ± 7 (26) 320 ± 9 (26) 24…”
mentioning
confidence: 94%
“…There were also no significant treatment effects in the sensitivity analysis that excluded all animals that overlapped with animals treated with 250,000 μg BPA/kg bw/day (see Materials and Methods, Statistical Methods). 474 ± 11 (50) 459 ± 11 (49) 477 ± 11 (46) 497 ± 13 (49) 506 ± 10 49482 ± 11 (47) 496 ± 12 (50) 480 ± 12 (49) 495 ± 12 (45) 516 ± 14 (48) 524 ± 11 (46) 502 ± 11 (47) 515 ± 12 (50) 496 ± 12 (48) 513 ± 14 (44) 536 ± 15 (48) 549 ± 13 (45) 520 ± 12 (47) 537 ± 12 (50) 517 ± 13 (48) 533 ± 15 (43) 558 ± 16 (47) 573 ± 13 (44) 540 ± 13 (43) 546 ± 13 (46) 537 ± 14 (47) 550 ± 15 (39) 571 ± 18 (44) 580 ± 13 (39) 552 ± 14 (41) 561 ± 14 (44) 556 ± 16 (45) 552 ± 14 (35) 570 ± 19 (36) 598 ± 14 (40) 568 ± 15 (39) 574 ± 15 (41) 568 ± 16 (41) 575 ± 16 (35) 576 ± 18 (34) 619 ± 15 (39) 575 ± 15 (35) 586 ± 18 (36) 580 ± 17 (38) 589 ± 16 (35) 588 ± 21 (31) 633 ± 18 (32) 601 ± 18 (30) 605 ± 19 (34) 591 ± 19 (36) 604 ± 19 (31) 595 ± 22…”
mentioning
confidence: 99%